2007
DOI: 10.1109/pes.2007.385694
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Exciter Voltage Limit to Power System Small Signal Stability Region

Abstract: We investigate the influence of non-differential components to the power system small signal stability region in this paper. A method named unified expression function (UEF) is introduced to describe the piecewise, continuous and nondifferential function in the small signal stability study. It converts non-differential points of the original function to poles of the UEF's derivative function. Then the derivative at those poles can be approximated by UEF's left-hand or right-hand derivative limits according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…2 of Lithuanian power plant. Small signal stability analysis allows simulate transients of the linearized model [4]. The analysis shows if the generator operates at rated conditions (P * = 1; Q * = 0.85; U * = 1, where P * and Q * are the active and reactive output power in p.u.…”
Section: B Stability Analysismentioning
confidence: 99%
“…2 of Lithuanian power plant. Small signal stability analysis allows simulate transients of the linearized model [4]. The analysis shows if the generator operates at rated conditions (P * = 1; Q * = 0.85; U * = 1, where P * and Q * are the active and reactive output power in p.u.…”
Section: B Stability Analysismentioning
confidence: 99%
“…In this case, the system may lose its stability well before the point of collapse is reached. An extension to this study was presented in [9] by investigating the impact of the exciter voltage limit. It was found that these limits change the feasibility boundary and produce a new hole inside the feasibility region, such that the topological characteristic of this region become even more complicated.…”
Section: Introductionmentioning
confidence: 99%